Endoscopic fenestration combined with catheterization in the treatment of a giant colonic fecalith causing bowel obstruction: a case report - Yang, Dong; Wang, Xueshan; Tao, Ke; Zhao, Huihui; Meng, Xiangwei (Zeitschrift für Gastroenterologie, 2022)
Obstruction of the colon caused by a fecalith is not a rare condition, but endoscopic attempts at removal of the fecalith are often unsuccessful because of the size of the fecalith and its extremely hard stone-like consistency. We report a case of bowel obstruction of over two weeks’ duration caused by a giant colonic fecalith. Conservative treatments including insertion of a gastric tube and enemas failed to resolve the obstruction. After an initial unsuccessful attempt at fecalith removal by colonoscopy using a snare, we successfully resolved the bowel obstruction over the course of subsequent colonoscopies with endoscopic fenestration of the fecalith and placement of a transrectal gastric tube for directed instillation of the enema fluid, and we were able to avoid surgical intervention in this case.
Keywords: Riesen-Kolonfäkalit; endoskopische Fenestration; Katheterisierung